2011
DOI: 10.1111/j.1468-1331.2011.03372.x
|View full text |Cite
|
Sign up to set email alerts
|

The incidence and prevalence of idiopathic intracranial hypertension in Sheffield, UK

Abstract: A higher incidence of IIH than previously reported UK data was found, which may be because of increasing obesity within the population, or improved case ascertainment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
94
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(105 citation statements)
references
References 18 publications
5
94
1
5
Order By: Relevance
“…1 It is a disease linked with obesity, and, in line with increasing levels of obesity in the population, its incidence is increasing. 2 Its importance lies in the fact that it can lead to irreversible vision loss. 3 To date, there are key unanswered questions in the management of IIH in terms of both the aetiology and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…1 It is a disease linked with obesity, and, in line with increasing levels of obesity in the population, its incidence is increasing. 2 Its importance lies in the fact that it can lead to irreversible vision loss. 3 To date, there are key unanswered questions in the management of IIH in terms of both the aetiology and its treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Women are more affected than men, 4 to even 15 times, as has been estimated (4). The frequency of IIH occurrence is 1-2 per 100.000 of the general population, and it is highest in the population of obese women (5). The estimations show that the total IIH widespread presence corresponds to the rate of obesity in an area (1).…”
Section: Introductionmentioning
confidence: 80%
“…The visual impairment due to IIH is the most serious complication (1,5). Considering that the time for these complications can be relatively long, even longer than five years, a long-term follow-up of patients is necessary, even in the cases of good primary response to therapy and the absence of other clinical manifestations of IIH (41,45).…”
Section: Scientificmentioning
confidence: 99%
“…It is increasing in incidence in parellel with the current epidemic of obesity 4,5 . Generally causes of IIH are endocrine 6 like adrenal insuffiency, cushings syndrome, hypoparathyroidism, hypothyroidism and hyperthyroidism, drugs like doxycycline,levothyroxine,lithium,nitrofurantoin,tamoxifen,tetracycline,pancreatin and chronic renal failure and SLE 7 . A case control study has found a strong association between IIH and obesity and with weight gain during the 12 months before the IIH diagnosis.…”
Section: Discussionmentioning
confidence: 99%